2016
DOI: 10.1021/acs.orglett.6b00804
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Cascade Reaction via Intramolecular Hydroamination Cyclization of Homopropargylic Amines and Intermolecular Povarov Reaction with Imines

Abstract: A new one-pot cascade reaction of homopropargylic amines with simple imines is developed in the presence of Cu(OTf)2 and affords a series of hexahydro-1H-pyrrolo[3,2-c]quinoline derivatives in good to high yields. This reaction proceeds through an intramolecular hydroamination cyclization of homopropargylic amine to generate a highly reactive dihydropyrrole intermediate in situ. It subsequently reacts with imine via an intermolecular inverse-electron-demand aza-Diels-Alder reaction and a 1,3-H shift to give th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…We initially tried reacting 10 with 9 to synthesize ac ross azine, but this did not result in any conversion of 9 after 24 hrs. In addition, reacting p-tolyl aldamine [71] with both 9 and in as toichiometric reactionw ith 10 did not result in conversion or deviation from the same results, respectively.I nt he case of cyclopropanation,t he mechanism is proceeds through an on-synchronous iron(II)-mediated transfer to the alkene, and not through an iron(IV) radical-mediated pathway. [72] The lack of reactivity,t herefore, gives an indication that the necessary electronics for compound 9 are incompatible for cyclopropanation.…”
Section: Hnmrmentioning
confidence: 71%
“…We initially tried reacting 10 with 9 to synthesize ac ross azine, but this did not result in any conversion of 9 after 24 hrs. In addition, reacting p-tolyl aldamine [71] with both 9 and in as toichiometric reactionw ith 10 did not result in conversion or deviation from the same results, respectively.I nt he case of cyclopropanation,t he mechanism is proceeds through an on-synchronous iron(II)-mediated transfer to the alkene, and not through an iron(IV) radical-mediated pathway. [72] The lack of reactivity,t herefore, gives an indication that the necessary electronics for compound 9 are incompatible for cyclopropanation.…”
Section: Hnmrmentioning
confidence: 71%
“…Initially, we selected 4‐bromo‐ N ‐(1‐phenylbut‐3‐yn‐1‐yl)aniline ( 1a ) and indole 5a as model substrates. Under the optimal reaction conditions previously developed,[7a] the unexpected 3‐pyrrolidine substituted indoles 6aa and 6aa′ were obtained in moderate yields (Table , entry 1). Screening the counterion cation of Cu 2+ salt, such as Cu(OAc) 2 , CuCl 2 and CuBr 2 , did not lead to any improvement in the results (entries 2–4).…”
Section: Resultsmentioning
confidence: 98%
“…Gold‐catalyzed intramolecular hydroamination cyclization cascade reactions of homopropargylic amines or amides have been successfully developed . Our research group has reported various cascade reactions of homopropargylic amines 1 in the presence of copper salts and provided simple and facile synthetic routes for the construction of complex fused N‐containing heterocycles (Scheme ) . Among these reactions, the key cycloenamine or cycloiminium intermediate was involved to act as 2C synthon or 4C synthon, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 2 presumably arises via initial aldimine formation followed by an intramolecular hydroamination of the activated aldimine C=N double bond using the pendant amine group . The Lewis acid‐mediated and metal‐catalyzed intramolecular hydroamination of imines to give 5‐ and 6‐membered heterocycles is an area of considerable recent interest …”
Section: Resultsmentioning
confidence: 99%